Numeracy of Eighth Grade Students in Solving AKM-Like Problems Based on Mathematical Ability - Zenithe Wahyudistya; Rooselyna Ekawati; Dayat Hidayat (Program Studi S1 Matematika UNESA, 2023)
Abstract: Numeracy is the ability to locate, use, interpret, evaluate, and communicate mathematical information and ideas in the real context. This research purpose to describe the numeracy of eighth grade students in solving AKM-like problems in equations and inequalities subdomain based on high, moderate, and low mathematical abilities. The research subjects were eighth grade students consisting of one student with high mathematical ability, one student with moderate mathematical ability, and one student with low mathematical ability. The research method used in this research is qualitative descriptive research. Data were obtained by numeracy test. Students with high mathematical abilities present the information obtained in the form of equations and inequalities, use mathematical rules and procedures on equations and inequalities, interpret the results in the context of the problem, evaluate the results of problem solving through supposed, and communicate the results of their interpretation to others both orally and writing appropriately. Students with moderate mathematical abilities present the information obtained in the form and use procedures and rules of equations and inequalities in solving problems appropriately. However, students with moderate mathematical abilities interprets the results inaccurately so that in communicating the results of the interpretation is also inaccurate and evaluate the results only by correcting or recalculating. Students with low mathematical abilities do not present information in the form of equations and inequalities, nor do they use procedures and rules of equations and inequalities in solving problems. The interpretation of students with low mathematical abilities is also incorrect so that communicating the results of interpretations is not correct. In addition, students with low mathematical abilities do not evaluate the results of problem solving, either through supposed or correcting and recalculating.